Can Conditional Cash Transfers Compensate for a Father's Absence? - Fitzsimons, Emla; Mesnard, Alice (World Bank, Washington, DC, 2013)
This paper investigates how the permanent departure of the father from a household affects children's school enrollment and work participation in rural Colombia. The results indicate that the permanent departure of the father decreases children's school enrollment by approximately 5 percentage points and increases child labor by 3 percentage points. This paper explores the rollout of a conditional-cash-transfer program during the period of study and shows that this program counteracts these adverse effects. When coupled with other evidence, this finding strongly suggests that the channel through which the father's departure most affects children is by reducing the income of very poor households, which tightens their liquidity constraints. This finding also highlights the important safety-net role played by welfare programs with respect to disadvantaged households, particularly because these households are unlikely to have formal or informal mechanisms with which to insure themselves against such vagaries.